Potential Erosion in Mining, Oil Palm Plantations, and Watersheds Reforestation Areas - Ahmad Syarif Sukri; M. Saripuddin; . Nasrul; Romy Talanipa (Civil Engineering Journal, 2023)
Erosion forecasting is a complex issue generated by numerous causes, the extent of which varies based on the unique area and conditions. Changes in rainfall, land cover, and watershed function are the primary causes of increased erosion. This study aims to scrutinize the actual and potential erosion in the mining area (MA), oil palm plantations (OPP), and watersheds reforestation (WR) in Asoloe, South Konawe, Indonesia. We utilized qualitative research methods and surveys with the USLE model. MA shares the highest actual erosion with 332.30 tons/ha/year, with an average erosion of 27.69 tons/ha/year from 2011 to 2022. Meanwhile, the potential erosion is 4747.19 tons/ha/year, with an average of 395.60 tons/ha/year. In terms of current conditions, 44.6% of rainfall engenders erosion with more than 0.5 t/ha and 33.9% with more than 1 t/ha. This study successfully demonstrates that for given location and area characteristics, high amounts of rainfall and changes in land function eminently affect soil erosion and that the potential erosion changes that occur in the Asoloe watershed every year are exceptionally influenced by changes in land use and land function. Therefore, some mitigation strategies and policies must be taken to reduce the risk of future erosion.Â Doi: 10.28991/CEJ-2023-09-09-07 Full Text: PDF